The Role of NGO Rifka Annisa in Violence Against Women During The COVID-19 Pandemic - Maisarah Mitra Adrian; Suswanta Suswanta; Elsa Septia (Universitas Sultan Ageng Tirtayasa, 2022)
: The purpose of this research is to determine the role of Rifka Annisa, a women's NGO, in responding to cases of violence against women in the city of Yogyakarta during the COVID-19 pandemic. Yogyakarta was chosen due to an increase in cases of violence against women. This is a qualitative study with a descriptive approach. The data used in this study is secondary data obtained from online media, websites, and related scientific articles that was then processed using NVivo 12 Plus software. The finding showed Rifka Annisa's role in cases of violence against women, with a focus or orientation on victims in three ways. The first is empowerment; the second is legal assistance; and the third is stigma reduction. According to the findings of the research, Rifka Annisa functions as an NGO, particularly in the non-political field, with a focus on empowering victims of violence.